Considerações sobre o espaço : do espaço mítico à espacialidade - Serrano, Pedro Pires, 1991- (2017)
The objective of this work lies in the issues of space in sculpture. It crosses a path through the various territories of modernism until postmodernism, evoking those who have had the most influence for an awareness and perception of space and the place of sculpture up to the present day. This dissertation addresses sculptors such as Richard Serra, Robert Morris, Robert Smithson, Anish Kapoor, Henri Moore, Vito Acconcci, among others artists whose work refers directly to space as main motto. In order to obtain a better understanding of this subject this investigation attempts to define the concept of space, in its mystical and physical relationship, and than evolving for technical references (construction, installation, exposition, among others), problematizing the direct relation with the body, with the object and with the space. In this way, we delimit a journey through the twentieth century, passing through the emergence of the happening (in it´s performance consecration), of constructivism, minimalism and site-specif and, as clutching units, references to cubism, environment, unism, process art and land art